Public administration traditions of inquiry and philosophies of knowledge - Riccucci, Norma (Washington, D.C Georgetown University Press, 2010)
Is public administration an art or a science? This question of whether the field is driven by values or facts will never be definitively answered due to a lack of consensus among scholars. The resulting divide has produced many heated debates; however, in this pioneering volume, Norma Riccucci embraces the diversity of research methods rather than suggesting that there is one best way to conduct research in public administration.
Includes bibliographical references and index.
Keywords: Public administration